KREATIVITAS SISWA SMP DALAM MENYELESAIKAN MASALAH MATEMATIKA TERBUKA DITINJAU DARI KEMAMPUAN MATEMATIKA - Laduni Laduni (Universitas Khairun, 2017)
ABSTRACTThis research is a descriptive qualitative research that attempts to describe students’ creativities based on mathematics ability in solving Open ended Problem in Mathematics. The creativity in this study is based on three indicators of creativity namely, fluency, flexibility and novelty. This study took places in SMP Negeri 1 Praya Barat Daya, Kabupaten Lombok and the subject of this research is the 8th graders. The subjects are consisted of three students with lower, middle, and highest ability. The steps of this research is started from the selection of research subjects which are determined based on tests of mathematical ability (TKM), then continued with the task in solving opened-problem in Mathematics (TMMMT) and interviews. Meanwhile, the validity of the data is done by using time triangulation through giving the similar task in solving opened-problem in Mathematics (TMMMT). The results of this research show that: (1) the creativity of lower level of student in solving mathematical opened-problem is the fulfillment of one indicator which is fluency. (2) the creativity of middle level of student in solving the mathematical opened-problem is the fulfillment of 2 indicators which are fluency and flexibility. (3) the creativity of the highest level of student in solving the Open ended Problem in Mathematics is the fulfillment of all indicators which are fluency, flexibility, creativity and novelty..Key Words: Creativity, Open ended Problem, Mathematical ability